(12x+1)/4=(13x-1)/5+3

Simple and best practice solution for (12x+1)/4=(13x-1)/5+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (12x+1)/4=(13x-1)/5+3 equation:



(12x+1)/4=(13x-1)/5+3
We move all terms to the left:
(12x+1)/4-((13x-1)/5+3)=0
We calculate fractions
(60x+5)/()+(-((13x-1)*4)/()=0
We calculate terms in parentheses: +(-((13x-1)*4)/(), so:
-((13x-1)*4)/(
We multiply all the terms by the denominator
-((13x-1)*4)
We calculate terms in parentheses: -((13x-1)*4), so:
(13x-1)*4
We multiply parentheses
52x-4
Back to the equation:
-(52x-4)
We get rid of parentheses
-52x+4
Back to the equation:
+(-52x+4)
We get rid of parentheses
(60x+5)/()-52x+4=0
We multiply all the terms by the denominator
(60x+5)-52x*()+4*()=0
We add all the numbers together, and all the variables
(60x+5)-52x*()=0
We get rid of parentheses
60x-52x*()+5=0
We move all terms containing x to the left, all other terms to the right
60x-52x*()=-5

See similar equations:

| 3b-9=4b+4 | | 3x²=6x+9 | | 35-4x=7-8 | | 6x+36+5x-14+3x-10+4x+10+6x+26=360 | | 3z/10-5=-7 | | 15=2(y+2) | | 5y=21-6=5y/5=15/5=3 | | 3(2x+7)=4-2(x-14) | | 4x-25+3x+15+4x+2x-3+3x+25=540 | | 2n=5+3=2n/2=8/2=4 | | 7x+40+6x+10+3x-10+4x+35+6x+25=360 | | 2n=5+3. | | 70=3x=55 | | 16(3x)-10(4x-8)=40 | | 2n=5+3 | | x+10=3x+10=6x-20 | | 180-(5x+x)=2x | | x+(x²+4)/5=2 | | y3+3y-0.015625=0 | | 18a²+8a=0 | | 1000000=3×2^x | | 36=l/9 | | 1000000/3=2^x | | 15+3x=-24 | | -25=5k | | 40=f-5 | | 7x–2=-23 | | 7x–2=-23* | | 3x=4x2+8 | | 4x+10=2x+2x=2 | | 2(q+4)=+3 | | -1,333y+6y=15-17 |

Equations solver categories